Why Do Easterners Have Lower Well-Being Than Westerners? The Role of Others' Approval Contingencies of Self-Worth in the Cross-Cultural Differences in Subjective Well-Being. (February 2017) - Liu, Cheng-Hong; Chiu, Yi-Hsing Claire; Chang, Jen-Ho
Previous studies have shown that Easterners generally perceive themselves as having lower subjective well-being compared with Westerners, and several mechanisms causing such differences have been identified. However, few studies have analyzed the causes of such differences from the perspective of the cross-cultural differences in the meanings of important life events such as whether people receive approval from others. Specifically, events regarding others' approval might have different meanings to and influences on Easterners and Westerners. Thus, the degree of fluctuation of people's views of self-worth in response to these events (i.e., others' approval contingencies of self-worth [CSW]) probably differs between Easterners and Westerners. This may be a reason for cross-cultural differences in subjective well-being. We investigated two samples of undergraduate students from Taiwan and the United States to examine the mediating role of others' approval CSW in forming cross-cultural differences in subjective well-being. The results revealed that Taiwanese participants exhibited lower subjective well-being and higher others' approval CSW than American participants. In addition, others' approval CSW partially mediated the cross-cultural differences in subjective well-being. Thus, one reason for lower subjective well-being among Easterners was likely that their self-esteem was more prone to larger fluctuations depending on whether they receive approval from others in everyday life.